Pengaruh Promosi terhadap Keputusan Pembelian Pada Merville Cafe di Kabupaten Bireuen - Nurmasyitah Nurmasyitah; Yusrawati Yusrawati; Al Mahfud Saputra (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
This study aims to analyze the effect of promotion on consumer purchase decisions at Merville Café in Bireuen Regency. The study employs a quantitative approach with an associative research design. A total of 99 respondents were selected using an accidental sampling technique. Data were collected through a structured questionnaire using a 5-point Likert scale. The data analysis techniques included validity and reliability tests, descriptive statistics, classical assumption tests, simple linear regression analysis, t-test, and coefficient of determination (R²). The results indicate that promotion has a positive and significant effect on purchase decisions, as evidenced by a regression coefficient of 0.644 and a significance value of 0.000. Furthermore, the coefficient of determination (R²) of 0.274 shows that promotion explains 27.4% of the variation in purchase decisions, while the remaining 72.6% is influenced by other factors outside the research model. These findings suggest that promotion plays an important role in influencing consumer purchase decisions in the culinary business sector. Therefore, Merville Café is recommended to implement more strategic, consistent, and creative promotional activities to enhance consumer attraction and improve purchase decisions.